Dyskretna uwodzicielska moc seriali - Mateja, Bogumiła (Kultura i Społeczeństwo, 2010)
The author attempts to describe the “struggle” between recipient and creator in the context of those studies of the media which see the crucial process as not only “what the media do to people”, but also “what people do with the media”. Prominence is given to the subtle mechanisms of the game played by viewers of soap opera serials. On the basis of these studies describes how the viewers create their own “individual rules of watching” Polish soap operas (such as the popular M jak miłość [“L as in Love”]) and use different means of distancing themselves from the watched serial (which in the article is described as the „I watch it but…” tactic). The analysis of the above mechanisms allows attempting to answer the question to what degree active reception protects the viewer from the influence of the serial?